An indicator of the need for regional integration - (:unkn) unknown (My University, 2014)
Because of the small demographic and economic size of most African countries, the great need for regional integration in Africa is widely recognised. The shortfall in regional infrastructure, be that in telecommunications, transport, or energy supplies, contributes to the low amount of transactions between African countries (even neighbouring countries), and to their relatively low economic growth rates. A recent study on the potential economic gains of more integration of countries within certain African country groupings evaluates these gains to be close to 2%.
Keywords: African Research